Congenital Hypopituitarism due to POU1F1 Gene Mutation - Ni-Chung Lee; Wen-Yu Tsai; Shinn-Forng Peng; Yi-Ching Tung; Yin-Hsiu Chien; Wuh-Liang Hwu (Journal of the Formosan Medical Association, 2011)
POU1F1 (Pit-1; Gene ID 5449) is an anterior pituitary transcriptional factor, and POU1F1 mutation is known to cause anterior pituitary hypoplasia, growth hormone and prolactin deficiency and various degree of hypothyroidism. We report here a patient who presented with growth failure and central hypothyroidism since early infancy. However, treatment with thyroxine gave no effect and he subsequently developed calf muscle pseudohypertrophy (Kocher-Debre-Semelaigne syndrome), elevation of creatinine kinase, dilated cardiomyopathy and pericardial effusion. Final diagnosis was made by combined pituitary function test and sequencing analysis that revealed POU1F1 gene C.698T > C (p.F233S) mutation. The rarity of the disease can result in delayed diagnosis and treatment.